Correction: A smartphone-based three-in-one biosensor for co-detection of SARS-CoV-2 viral RNA, antigen and antibody. Issue 48 (1st June 2022) - Dou, Yanzhi; Su, Jing; Chen, Shixing; Li, Tie; Wang, Lihua; Ding, Xianting; Song, Shiping; Fan, Chunhai
Abstract : Correction for 'A smartphone-based three-in-one biosensor for co-detection of SARS-CoV-2 viral RNA, antigen and antibody' by Yanzhi Dou et al., Chem. Commun., 2022, DOI: ; https://doi.org/10.1039/d2cc01297a .